Overview of quantum key distribution metropolitan optical networking technology - Hua WANG; Yongli ZHAO (Tongxin xuebao)
Quantum key distribution is a basic implementation technology of quantum communication,which provides a secure key distribution method.With the maturity and development of point-to-point quantum key distribution technology,multi-point to multi-point quantum key distribution networking has become a trend of development in the future.How to construct a multi-point to multi-point quantum key distribution network is currently urgent problem.The architecture of QKD-MON was proposed,the key problems and corresponding strategies in QKD-MON were discussed,the applications of QKD-MON in various scenes were studied,and finally the future development direction and challenges were discussed.The QKD network architecture proposed can efficiently implement QKD between multiple points and provide key resources for the customer flexibly.